A comparative study on effect of feed mixture on fingerling growth of Siganus luridus & Siganus rivulatus, reared in tanks - شحود أنس; أمير إبراهيم; معينة بدران (Latakia University Journal -Biological Sciences Series, 2022)
This study aimed to know the effect of using plant and animal feed mixtures with 30% protein ratio on fingerling growth of two species of fish, Siganus rivulatus and Siganus luridus. The fingerlings were distributed in eight polyethylene tanks with a density of 12 fish/tank, and fed twice a day. The hydrological parameters were taken daily at 10 a.m., and the length and weights of fingerlings were taken three times during 62 days. The result showed that the animal feed was suitable for the growth of the two types of fish during this age, where the fingerling was more likely to reach the best average of growth depending on this feed. The average weight of fish fed with animal feed was 17.75±0.9g for Siganus rivulatus and 21.25±0.5g for Siganus luridus, While the average weight of fish fed with plant feed was 13.38±0.6g for Siganus rivulatus and17.5±0.3g for Siganus luridus. The feed conversion ratio tends to be better for the fish which was fed with animal feed as it was equal to 1.69% for Siganus rivulatus and 1.55% for Siganus luridus while it was 2.1% for Siganus rivulatus and 1.71% for Siganus luridus when fed on plant feed.